Processos históricos e padrões globais de diversidade em aves de rapina diurnas - Simon, Lorena Mendes (2015)
The latitudinal gradient of diversity is a ubiquitous pattern in natural world, but the determining factors of this pattern varies among different groups of organisms and geographical scales. Diurnal raptors exhibit a strong tendency of global species increase toward the tropics and share morphological characteristics. Despite the similarities, they were recently subdivided into two different orders (Falconiformes and Accipitriformes) which had their ancestral origin in different biogeographical regions, but predominantly tropical. To assess whether the orders retained their ancestral tropical condition, we used molecular phylogenies to classify species between basal and derived, which were related to total species richness later. Additionally, we used the GeoSSE algorithm to estimate speciation, extinction and dispersion rates associated with tropical and extratropical regions in order to understand the dynamics of diversity throughout their evolutionary histories. We found that both orders showed a strong relation between current richness and basal species, suggesting a conservation of the tropical niche in oldest. We also found higher rates of speciation and dispersal in temperate regions, whereas extinction rates did not differ between regions. In both orders the diversification was low in tropical and extratropical regions, and the dispersion rates were determinant driving the range expansion of species toward the tropics. These results suggest that despite the different ancestral areas of origination, both Falconiformes and Accipitriformes share similar process underling the pattern of latitudinal richness distribution seen nowadays, predominantly influenced by tropical niche conservatism and high dispersal rates toward the tropics.